Post-market safety profile and suicide/self-injury risk signals of dextromethorphan/bupropion: a real-world pharmacovigilance study. - Yuan, Lingjing; He, Jianping; Li, Xiangyu (European Journal of Clinical Pharmacology, 2025)
Background: Dextromethorphan/bupropion (D/B) is an innovative pharmacological treatment for major depressive disorder. Nevertheless, the current evidence regarding the safety profile of D/B is predominantly derived from clinical trials, thus hindering the timely updating of adverse event (AE) data for this medication. Therefore, this study conducted data mining and analysis of AE signals (especially for suicide/self-injury) associated with D/B using the Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: This study used the disproportionality method to systematically evaluate the associations between D/B and potential AEs and compared these AEs with AEs related to bupropion and esketamine by using data from the FAERS collected between the third quarter of 2022 and the second quarter of 2024. Results: A total of 2451 AE reports identifying D/B as the "primary suspect" were collected. From these reports, 81 preferred terms and 24 system organ classifications were identified, with a predominant focus on psychiatric disorders (22.07%) and nervous system disorders (18.77%). These AEs were mostly found in individuals aged 18–44 years. The median time to onset for D/B-related AEs was determined to be 2 days. Nearly 20 novel AEs identified during the labelling process were detected, such as a sensation of inebriation and panic attacks. Importantly, the risk signals for suicide/self-injury associated with D/B were significantly lower than those associated with bupropion and esketamine. However, these signals cannot be ignored in view of their serious consequences. Conclusion: Psychiatric and nervous system disorders, such as suicidal/self-injurious behaviours, require careful monitoring in clinical applications. It is imperative to conduct traditional pharmacoepidemiological research to evaluate whether D/B is linked to an increased risk of dissociative disorders in the future. Moreover, health care professionals should remain vigilant for AE signals not listed in package inserts.